Game-Based Exercises That Aid In The Development Of Students’ Emotional Intelligence While Learning Chess - Khachatryan, Armine; Sargsyan, Anzhela (Զանգակ հրատ.)
In 2017, the “Chess” Scientific Research Institute’s research group of psychologists performed a diagnostic experiment to determine the level and manifestations of emotional intelligence of teachers and students during the teaching and learning of the “Chess” subject. The findings of the preceding investigations were presented at the international conference “Current State and Development Trends in Chess Education,” which was held in Tsaghkadzor in 2019. The following findings were offered after summarizing the outcomes of all methods used throughout the scientific experiment: 1. Chess teachers have a high level of emotional awareness, whereas children may distinguish just pleasure, sadness, and anger as fundamental emotions. 2. Low indicators of the teacher’s empathy and emotional management affect the motivation of 3rd and 4th-grade students to succeed in chess lessons, as well as the negative trend of the position of receiving praise from the teacher, as a result of which the indicator of the manifestation of a favorable position towards the chess teacher decreases. 3. Regardless of the teacher’s positive attitude toward the students, if the teacher’s emotional management and control signs are poor throughout the learning process, the student’s emotional attitude toward their peers and their participation in the chess class diminishes. Based on the analysis of the diagnostic experiment findings, “Chess” Scientific Research Institute psychologists created and tested various game exercises to develop emotional intelligence components in secondary school learners.
Keywords: Psychology